2018
DOI: 10.1037/per0000276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical severity as a moderator of outcome in psychodynamic and dialectical behavior therapies for borderline personality disorder.

Abstract: The aim of the present study was to assess the effect of initial level of psychiatric severity on treatment outcome in psychodynamic therapy and dialectical behavior therapy (DBT) for borderline personality disorder (BPD). It was hypothesized that DBT would lead to better outcome for patients with high psychiatric severity, whereas dynamic treatment would lead to better outcome for patients with lower psychiatric severity. Data from the 5th-year follow-up of the Stockholm City Council's and the Karolinska Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…For instance, it is unclear whether the currently recommended evidence based psychosocial treatments [2] should be applied in all BPD patients, or whether a differential indication based on symptom severity might reveal better treatment results. In particular, the studies by Bateman & Fonagy [3] and by Sahin et al [4] indicate that the relative efficacy of treatments might be moderated by the severity of the disorder. Accordingly, most clinicians and researchers agree, that in addition to the categorical diagnostic, the severity of the disorder should be defined.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is unclear whether the currently recommended evidence based psychosocial treatments [2] should be applied in all BPD patients, or whether a differential indication based on symptom severity might reveal better treatment results. In particular, the studies by Bateman & Fonagy [3] and by Sahin et al [4] indicate that the relative efficacy of treatments might be moderated by the severity of the disorder. Accordingly, most clinicians and researchers agree, that in addition to the categorical diagnostic, the severity of the disorder should be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial determination of efficacy and effectiveness of DBT for adolescent eating disorders, it will be important to determine for whom DBT may be best suited. We recommend that researchers and clinicians use existing moderator research in DBT for other presenting problems (e.g., Sahin et al, 2018) as a starting point for determining for whom DBT is most effective. We also recommend that researchers and clinicians consider a range of clinical characteristics-diagnostic, demographic, developmental, or psychological-that may indicate or contraindicate the use of DBT or influence outcome.…”
Section: Summary Of Existing Work and Future Directionsmentioning
confidence: 99%
“…In addition to naturalistic research, clinical trials of psychotherapeutic interventions for BPD have recently shown greater interest in their long-term outcomes, reporting follow-up data for five years or more [19, 20, 21, 22, 23]. This longitudinal perspective on efficacy studies underlines the relevance of treatment as a potential factor of change over time.…”
Section: Introductionmentioning
confidence: 99%